Windows of Integration Hypothesis Revisited - Hirschhorn, Rony; Kahane, Ofer; Gur-Arie, Inbal; Faivre, Nathan; Mudrik, Liad (Frontiers in Human Neuroscience, 2021)
In the ongoing research of the functions of consciousness, special emphasis has been put on integration of information: the ability to combine different signals into a coherent, unified one. Several theories of consciousness hold that this ability depends on – or at least goes hand in hand with – conscious processing. Yet some empirical findings have suggested otherwise, claiming that integration of information could take place even without awareness. Trying to reconcile this apparent contradiction, the ‘windows of integration’ hypothesis claims that conscious access enables signal processing over large integration windows. The hypothesis applies to integration windows defined either temporally, spatially or semantically. In this review, we explain the hypothesis and re-examine it in light of new studies published since it was suggested. In line with the hypothesis, these studies provide compelling evidence for unconscious integration, but also demonstrate its limits with respect to time, space and semantic distance. The review further highlights open questions that still need to be pursued to demonstrate the applicability of the ‘windows of integration’ hypothesis as a guiding principle for understanding the depth and scope of unconscious processes.